2010
DOI: 10.1210/en.2010-0177
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Rapidly Increases KATP Activity in GnRH via a Protein Kinase Signaling Pathway

Abstract: 17Beta-estradiol (E2) both inhibits and excites GnRH neurons via presynaptic as well as postsynaptic mechanisms. Although it has been demonstrated that E2 can alter the excitability of GnRH neurons via direct actions, the intracellular signaling cascades mediating these actions are not well understood. Previously we have shown that the activity of one of the critical ion channels needed for maintaining GnRH neurons in a hyperpolarized state, the ATP-sensitive potassium channel (K(ATP)) channel, is augmented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 51 publications
3
72
0
Order By: Relevance
“…Similar associations have been found between estrogen and K ATP channels in the neuroendocrine system [15,16]. Zhang et al [15] reported that 17b-estradiol could enhance K ATP channel activity in GnRH neurons through an ER-activated PKC-PKA signaling pathway. Neurons in the brain, like those of the myocardium, are excitable cells, and the K ATP channels can affect these neurons in similar ways.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similar associations have been found between estrogen and K ATP channels in the neuroendocrine system [15,16]. Zhang et al [15] reported that 17b-estradiol could enhance K ATP channel activity in GnRH neurons through an ER-activated PKC-PKA signaling pathway. Neurons in the brain, like those of the myocardium, are excitable cells, and the K ATP channels can affect these neurons in similar ways.…”
Section: Introductionsupporting
confidence: 59%
“…It has also been reported that 17b-estradiol increased the levels of SUR2A mRNA, the regulatory subunit of the K ATP channel, in heart-derived H9c2 cells [14]. Similar associations have been found between estrogen and K ATP channels in the neuroendocrine system [15,16]. Zhang et al [15] reported that 17b-estradiol could enhance K ATP channel activity in GnRH neurons through an ER-activated PKC-PKA signaling pathway.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The lack of an obvious reproductive phenotype of the GPER-knockout mice may have hindered research in this area, as the global knockout may have developmental compensation for physiological roles normally mediated by GPER and, as discussed above, the role of GPER may be different in primates [18, 22, 59, 60]. There are still substantial gaps in knowledge about the receptors that mediate positive and negative effects of estrogens on GnRH neurons, making the GPER of potential interest beyond ERα, ERβ and STX-sensitive receptors [22, 57, 61].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, E 2 regulation of GnRH cells was thought to be entirely indirectly mediated by other neuronal cell types and/or glia, because GnRH cells do not co-express estrogen receptor (ER) α [17]. GnRH cells are now known to contain ERβ, STX-sensitive estrogen receptors, and G protein-coupled membrane estrogen receptor (GPER, sometimes called GPR30) [1823]. Of these, membrane ERs enable GnRH cells to respond rapidly to E 2 with increased action potential rate, intracellular Ca 2+ oscillations, and GnRH peptide release [2327].…”
Section: Introductionmentioning
confidence: 99%